Practice of Cross-infection Control for Dental Impression in Commercial Dental Laboratory - Pradhan, Dilesh; Shrestha, Lajana; Lohani, Junu; Munankarmi, Jivesh (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Introduction: Dental professionals are at the risk of exposure to wide varieties of microorganisms from blood and saliva of patients to airborne infection from microbial-laden aerosols and spatter created during laboratory procedures. Dental laboratories are usually disregarded when planning effective infection and exposure control measures. Contaminated impression may act as a vehicle for transmission of infectious agents. Objective: The objective of this study was to assess the practice of dental technicians towards infection control and to evaluate practice of the same for dental impressions in commercial dental laboratories. Methods: Self-administered standard questionnaire was distributed to 35 dental laboratories and 31 participated in the study. The answers were collected by the investigators themselves. The data obtained were computed and analysed to find the results. Results: Among all dental laboratories, 21 (67.75%) ensure dental impression is disinfected in clinic. 18 (58.06%) wear gloves when receiving clinical items and 27 (87.10%) transfer the items in separate sealed plastic bag. Of all, 25 (80.64%) of the dental laboratories have separate receiving area for dental impression and 23 (74.19%) of the dental technicians continue to wear protective barriers (gloves, mask and apron) during work. In total, 29 (93.55%) of the dental laboratories confirmed, none of their technicians has ever attended any course or training in cross-infection control. Conclusion: The practice of cross-infection control for dental impression in commercial dental laboratories is acceptable. There should be proper guidelines from the regulating body on the protocol of infection control and laboratory waste disposal.